Enhancement of Optical Nonlinearity in Coupled Resonator Optical Waveguide Based on Slotted 1-D Photonic Crystal Cavity - Shuntaro Makino; Takeshi Fujisawa; Kunimasa Saitoh (IEEE Photonics Journal)
A coupled resonator optical waveguide (CROW) based on a slotted 1-D photonic crystal (1-D PC) cavity is proposed, and its enhancement of the optical nonlinearity due to the slow-light effect of the CROW and the small effective area of the slotted 1-D PC cavities is demonstrated. Setting the appropriate slot configuration in terms of the tradeoff between the nonlinear parameter and the leakage loss, a large nonlinear parameter exceeding $10^4\ \text{m}^{-1}\text{W}^{-1}$ can be obtained.